The transient stability analysis of wind turbines interconected to grid under fault - Anass Gourma; Abdelmajid Berdai; Moussa Reddak (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Wind farm has been growing in recent years due to its very competitive electricity production cost. Wind generators have gone from a few kilowatts to megawatts. However, the participation of the wind turbine in the stability of the electricity grid is a critical point to check, knowing that the electricity grid is meshed, any change in active and reactive flux at the network level affects its stability. With a rate of 50% wind turbine penetration into the electricity grid, the stability of the rotor angle is a dynamic phenomenon which is only visible by the variation of the active energy. The purpose of this journal is to verify the impact of wind turbine integration on an electrical grid, by exploiting the relationship between the reactive energy produced by the Doubly Fed Induction Generator equipping most wind energy systems, and the stability of the rotor angle of the synchronous generators equipping the conventional power plants in the electrical system.